The role of Emotional Intelligence in Psychological Adjustment among Adolescents - Cobos-Sánchez, Lidia; Flujas-Contreras, Juan M.; Gómez-Becerra, Inmaculada (Anales de Psicología / Annals of Psychology, 2016)
This research aims to analyse the role of emotional ingelligence and various psychological factors in school environment. This paper compare psychosocial factors from a school in social risk area with a school in normative area, where in 211 spanish adolescents with a average age of 13 years participated. The Bar-On Emotional Intelligence Inventory: Young Version (EQi:YV) and the Behavior Assessment Sysem for Children (BASC) were used. Differences in behavior problems were found according to school environment and emotional intelligence level. Furthermore, positive correlations between psychological adjustment and all scales from EQi:YV were found. Multiple regression models obtainted emphasized the influence of general mood and parents relationship as factors to psychological adjustment and emotional intelligence.